Detection and localization of Solitalea-like and Cardinium bacteria in three Acarus siro populations (Astigmata: Acaridae) - Hubert, Jan; Kopecky, Jan; Nesvorna, Marta; Alejandra Perotti, M; Erban, Tomas (Experimental & applied acarology, 2016)
Bacteria associated with mites influence their fitness, nutrition and reproduction. Previously, we found Solitalea-like (Sphingobacteriales) and Candidatus Cardinium (Cytophagales) bacteria in the stored product mite Acarus siro L. by cloning and using pyrosequencing. In this study, taxon-specific primers targeting 16S rRNA gene were used to detect and quantify the bacteria in mites and eggs of three A. siro populations. The specific probes for fluorescent in situ hybridization (FISH) were used to localize Solitalea-like and Cardinium bacteria in mite bodies. The population growth as an indirect estimator of fitness was used to describe the mite-bacteria interactions on (1) control diet; (2) rifampicin supplemented diet; (3) tetracycline supplemented diet; (4) rifampicin pretreated mites; (5) tetracycline pretreated mites. Solitalea-like 16S rRNA gene sequences from A. siro formed a separate cluster together with sequences from Tyrophagus putrescentiae. qPCR analysis indicated that number of Solitalea-like bacteria 16S rRNA gene copies was ca. 100× higher than that of Cardinium and the numbers differed between populations. FISH analysis localized Solitalea-like bacteria in the parenchymal tissues, mesodeum and food bolus of larvae, nymphs and adults. Solitalea-like, but not Cardinium bacteria were detected by taxon-specific primers in mites and eggs of all three investigated populations. None of the antibiotic treatments eliminated Solitalea-like bacteria in the A. siro populations tested. Rifampicin pretreatment significantly decreased the population growth. The numbers of Solitalea-like bacteria did not correlate with the population growth as a fitness indicator. This study demonstrated that A. siro can host Solitalea-like bacteria either alone or together with Cardinium. We suggest that Solitalea-like bacteria are shared by vertical transfer in A. siro populations.
Keywords: Acaridae; Symbiosis; RNA, Ribosomal, 16S; nymfa; Antibiotic treatment; Transmission of bacteria; Anti-Bacterial Agents; DNA, Bacterial; hybridizace in situ fluorescenční; Male; krmivo pro zvířata; mužské pohlaví; Bacteroidetes; In Situ Hybridization, Fluorescence; DNA bakterií; Symbiont; Stored product mites; ženské pohlaví; RNA ribozomální 16S; zvířata; Nymph; symbióza; genetická zdatnost; antibakteriální látky; Animal Feed; larva; Larva; Female; Genetic Fitness; Animals